Profile of Students' Mathematical Communication Skills in Solving Three-variable Linear Equation Systems Problems Assessed from Extroversion and Introversion Types of Personalities - Halima, Nur (Department of Mathematics Education , University of Jember, 2020)
One of the goals of learning mathematics is learning to communicate (mathematical communication). Mathematical communication skills are useful in gaining a better understanding of mathematics and a longer memory of learning mathematics. There are differences in communicating ideas, one of which is caused by differences in personality types. The personality types referred to in this study are extrovert and introvert personality types. This type of research is a qualitative descriptive study which aims to describe the profile of the extrovert and introvert students’ mathematical communication skills in solving the Three-Variable Linear Equation System question. This research was conducted in MAN 2 Jember and the research subject were all students of class X IPA 1. The data collection method used questionnaires and tests. The instruments used were personality type questionnaires, written test question, oral test question, and assessment rubrics. Based on the result of the analysis and discussion, it can be concluded that in general extrovert students and introvert students have similiarities and differences in written mathematical communication skills, namely extrovert students and introvert students alike can write down the information known from the questions, the type of methods to be used to solve the question, and use mathematical symbols. The differences is that introvert students can written down the steps for completion and conclusions, but not for extrovert students, this is because extrovert students end a job even though they have not found a solution. In analyzing a job, introvert students tend to take a long time, are more thorough, rushed, and give up easily in completing work. In general, it can be concluded that extrovert and introvert students can explain mathematical models from known information, state the type of methods to be used to solve problems, and used mathematical symbols. The difference is that extrovert students can explain the completion steps but not introvert students, this is because introvert students are hesitant and pessimistic, so they say cannot explain the completion steps even they not tried it.